Cross-layer host-network co-design for QoS in streamed video data networking - Nan, Ya (Nanyang Technological University, 2024)
With the surge in video applications, video traffic has become the dominant form of Internet traffic. Given their significant data size and the need for low-latency transmission, video data present considerable challenges to contemporary networking systems. We identify a pivotal research gap as the disjoint design of hosts and the network. To address this, we introduce the concept of host-network co-design, aiming at the enhancement of system performance through the coordination between hosts and the network. The research undertaken during my PhD delineates host-network co-design in two distinct scenarios, namely video analytics systems and general-purpose wide area networks.